'A singularly gifted man': A. D. 'Dave' Munrow and academic physical education at the University of Birmingham. Issue 1 (2nd January 2021) - Vertinsky, Patricia
ABSTRACT : 'I think our subject can light up one facet which universities in their very nature sometimes fail to see', said A.D. 'Dave' Munrow in his career-long quest to make physical education a subject worthy of study at Birmingham University. This paper follows Munrow's efforts in early post- war Britain to forge a Department of Physical Education that welcomed scientific enquiry and articulated new approaches to the training of sports skills and techniques while guarding against a cleavage between the sciences and humanities. Female students were admitted to the programme from its inception even while he challenged the emphasis of women's physical education colleges upon movement education and generalised skill training. His programme was well established by the time Franklin Henry at the University of California, Berkeley outlined the body of knowledge acceptable in a physical education degree, as was his substantial reputation on the international stage of physical education and sport, and as one of Britain's leading architects of sport. Upon his early death in 1975 he was eulogised as ' a genial spirit with a talent for subjecting views to critical examination'. 'In the field of physical education', said Walter Winterbottom, 'Dave Munrow was a singularly gifted man'.